Stereotip Peran Gender di Jaman Edo dalam Drama Asa ga Kita - Aulia Maulida Safitri (Universitas Diponegoro, 2023)
The Edo Period (1868-1912) was the era when Japan was under the rule of a class government or military group. The class system is also a feature of the Edo Period, known as the Shi-Nou-Kou-Sho system. The highest class is samurai or the military, while the lowest class is merchant. Those from the merchant class usually marry the merchant class in an arranged marriage system. Merchant class women had arranged marriages since they were children. The research in this study is how society views women who work in the Edo period, through the drama analysis unit Asa ga Kita. The theory used is Linda Brannon's theory of gender stereotypes. <a href=